Feasibility and Safety of Intra-arterial Pericyte Progenitor Cell Delivery following Mannitol-Induced Transient Blood-Brain Barrier Opening in a Canine Model. Issue 8 (August 2015) - Youn, Sung Won; Jung, Keun-Hwa; Chu, Kon; Lee, Jong-Young; Lee, Soon-Tae; Bahn, Jae-Jun; Park, Dong-Kyu; Yu, Jung-Suk; Kim, So-Yun; Kim, Manho; Lee, Sang Kun; Han, Moon-Hee; et al.
Stem cell therapy is currently being studied with a view to rescuing various neurological diseases. Such studies require not only the discovery of potent candidate cells but also the development of methods that allow optimal delivery of those candidates to the brain tissues. Given that the blood-brain barrier (BBB) precludes cells from entering the brain, the present study was designed to test whether hyperosmolar mannitol securely opens the BBB and enhances intra-arterial cell delivery. A noninjured normal canine model in which the BBB was presumed to be closed was used to evaluate the feasibility and safety of the tested protocol. Autologous adipose tissue-derived pericytes with platelet-derived growth factor receptor β positivity were utilized. Cells were administered 5 min after mannitol pretreatment using one of following techniques: (1 ) bolus injection of a concentrated suspension, (2 ) continuous infusion of a diluted suspension, or (3 ) bolus injection of a concentrated suspension that had been shaken by repeated syringe pumping. Animals administered a concentrated cell suspension without mannitol pretreatment served as a control group. Vital signs, blood parameters, neurologic status, and major artery patency were kept stable throughout the experiment and the 1-month posttreatment period. Although ischemic lesions were noted on magnetic resonance imaging in several mongrel dogs with concentrated cell suspension, the injection technique using repeated syringe shaking could avert this complication. The cells were detected in both ipsilateral and contralateral cortices and were more frequent at the ipsilateral and frontal locations, whereas very few cells were observed anywhere in the brain when mannitol was not preinjected. These data suggest that intra-arterial cell infusion with mannitol pretreatment is a feasible and safe therapeutic approach in stable brain diseases such as chronic stroke.